When do small countries win tax wars? - Wolfgang Eggert; Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
The paper analyzes the conditions under which the smaller of two otherwise identical countries prefers the non-cooperative Nash equilibrium to a situation of fully harmonized tax rates. A standard two-country model of capital tax competition is extended by allowing for transaction costs, additional countries, and additional tax instruments. The effects of introducing either mobility costs or a wage tax instrument are theoretically ambiguous because they lower both the costs and the benefits of non-cooperation from the perspective of the small country. Numerical simulations indicate, however, that for a wide range of parameter values all model extensions considered reduce the possibility that the small country gains from tax competition.
Keywords: H73; H77; F15; 330